Shifting Epidemiology of Infant Rotavirus Gastroenteritis in Pakistan Following Nationwide Vaccine Implementation: A Prospective Cohort Study - Nimrah Shehzadi, Muhammad Own Ali, Shahzad Mustufa, Umair Ul Hassan, Muhammad Usman, Sonia Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Rotavirus gastroenteritis has historically been a leading cause of severe diarrhea,dehydration, hospitalization, and mortalityamong infants in Pakistan. Following the nationwide introduction of the monovalentrotavirus vaccine into the Expanded Program